PENGEMBANGAN GAME EDUKASI BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI PERKALIAN UNTUK SISWA KELAS 3 SEKOLAH DASAR - Naftali Anggita Cahyani, Naftali; Agustini, Ferina; Cahyani, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student understanding of multiplication material in elementary school mathematics learning, caused by the use of less varied teaching methods and the lack of interactive learning media. This research aims to develop interactive multimedia-based educational game media for multiplication material and to determine its level of validity, practicality, and effectiveness in improving students' cognitive abilities. This study employs a Research and Development (R&D) method with the ADDIE development model, encompassing analysis, design, development, implementation, and evaluation stages. The research subjects were 21 third-grade elementary school students. Data collection techniques included observation, interviews, questionnaires, and tests. Data were analyzed using descriptive qualitative and quantitative techniques. The results indicate that the developed educational game media was declared valid based on assessments by material and media experts. Additionally, the media was deemed highly practical based on responses from teachers and students. Effectiveness testing showed an improvement in students' learning outcomes on multiplication material after using the learning media, as evidenced by higher posttest scores compared to pretest scores.